Extra-ampullary Peutz–Jeghers polyp causing duodenal intussusception leading to biliary obstruction: a case report. (December 2016) - De Silva, W.; Pathirana, A.; Gamage, B.; Manawasighe, D.; Jayasundara, B.; Kiriwandeniya, U.
Abstract Background Duodenal Peutz–Jeghers polyp is a rare cause of duodenal or biliary obstruction. However, a sporadic Peutz–Jeghers polyp leading to simultaneous biliary and duodenal obstruction has not been reported. Case presentation We report a case of a 25-year-old Sri Lankan woman presenting with features of recurrent upper small intestinal obstruction and biliary obstruction. She had clinical as well as biochemical evidence of intermittent biliary obstruction. Evidence of duodenal intussusception was found in a computed tomography enterogram and a duodenal polyp was noted as the lead point. Marked elongation and distortion of her lower common bile duct with intrahepatic duct dilatation was also noted and the ampulla was found to be on the left side of the midline pulled toward the intussusceptum. Open polypectomy and reduction of intussusception were done and she became fully asymptomatic following surgery. Histology of the resected specimen was reported as a typical "Peutz–Jeghers polyp". As there was not enough evidence to diagnose Peutz–Jeghers syndrome this was considered to be a sporadic Peutz–Jeghers polyp. Conclusion Rare benign causes such as a duodenal polyp should be considered and looked for in initial imaging, when the cause for concurrent biliary and intestinal obstruction is uncertain, particularly in young individuals.